Photon Green’s functions theory for Coulomb correlated quantum well lasers - Pereira Jr., M.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
A photon Green’s function theory is used to incorporate Bethe-Salpeter-like many body corrections in the computations of output spectra of semiconductor quantum well lasers. Coulomb, quantum-confinement, multiple valence band coupling and cavity resonator effects are consistently included in the theory. Numerical results are presented for multiple quantum wells, under different design, and excitation conditions.